The Gateway Reflex, a Novel Neuro-Immune Interaction for the Regulation of Regional Vessels - Tanaka, Yuki; Arima, Yasunobu; Kamimura, Daisuke; Murakami, Masaaki (Frontiers in Immunology, 2017)
The gateway reflex is a new phenomenon that explains how immune cells bypass the blood-brain barrier (BBB) to infiltrate the central nervous system (CNS) and trigger neuroinflammation. To date, four examples of gateway reflexes have been discovered, each described by the stimulus that evokes the reflex. Gravity, electricity, pain and stress have all been found to create gateways at specific regions of the CNS. The gateway reflex, the most recently discovered of the four, has also been shown to upset the homeostasis of organs in the periphery through its action on the CNS. These reflexes provide novel therapeutic targets for the control of local neuroinflammation and organ function. Each gateway reflex is activated by different neural activations and induces inflmammation at different regions in the CNS. Therefore, it is theoretically possible to manipulate each independently, providing a novel therapeutic strategy to control local neuroinflammation and peripheral organ homeostasis.